Aseptic inflammation as the essential link in the pathogenesis of endometrioid disease - Yu.A. Orlova; A.M. Hromova; O.M. Ketova; T.Yu. Liakhovska; V.B. Martynenko; E.I. Krutikova (Medičnì Perspektivi)
The paper was aimed at determination of the quantitative activity of iNOS and Arg1, as well as M1 and M2 phenotype macrophages in women with endometrioid disease to establish their role in the pathogenesis of endometriosis. A prospective study was performed in gynecological units of the medical facilities of Poltava city. 140 women of reproductive age who made up the main group (110 women with endometrioid disease) and the control group (30 women without endometrioid disease) voluntarily participated in the study. All women underwent planned surgical treatment for existing gynecological pathology. Before surgical treatment, women were examined in accordance with the current Orders of the Ministry of Health of Ukraine. The spectrophotometric method was used to determine the enzymatic markers of macrophages (in the endometrium and peritoneal fluid) polarized into M1(iNOS) and M2 (Arg1) phenotypes. The type of macrophages was determined individually in each patient according to the ratios: in iNOS>Arg1, the M1 macrophage type prevailed; in Arg1>iNOS, the M2 macrophage type prevailed. When examining endometrial samplings in women from the main group, the iNOS indicator was by 1.4 times higher compared to women from the control group. The obtained results at the stage of entry into the abdominal cavity showed that mostly women from the main group suffered from the pelvic adhesion, especially stage 3 and stage 4. Among the obtained results, the increased quantitative activity in the peritoneal fluid of both iNOS and Arg1 in women of the main group was significant compared to the control group. When comparing the stages of endometrioid disease to the rates of quantitative activity of macrophage enzyme markers (in peritoneal fluid), it was found that the increase in the stage of the disease (from stage 3 to stage 4) caused an increase in the quantitative activity of Arg1 by 1.9 times and a decrease in the quantitative activity of iNOS by 2.9 times. Therefore, the planning of surgical intervention for women with endometrioid disease should consider a significant percentage of the pelvic adhesive disease, especially at the severe stages. Initiation of the chronic aseptic inflammatory process in endometrioid disease is caused by an increased quantitative activity of iNOS in the endometrium. In the pathogenesis of endometrioid disease, the presence of M2 phenotype macrophages in the peritoneal fluid is important, while the switching of macrophage phenotypes from a pro-inflammatory subpopulation to an anti-inflammatory one is crucial.